KEDUDUKAN KONSUMEN DALAM KEPAILITAN (THE POSITION OF CONSUMER IN BANKRUPTCY) - Luthvi Febryka Nola (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2017)
Bankruptcy and suspension of obligation for debt repayment is one of dispute resolution mechanisms that can be chosen by parties with an aim of solving the problem in an economical and transparent manner. This mechanism is regulated in Law No. 37 of 2004 of Bankruptcy and Suspension of Obligation for Debt Repayment (Insolvency Law). However, the Law has faced many problems in its implementation mainly related to consumer protection. This paper will discuss consumer position related to bankruptcy and its implementation. The author finds that consumer position in bankruptcy is not only govern by Insolvency Law but also by the Civil Code, Law No. 8 of 1999 on Consumer Protection, and Law No. 40 of 2014 on Insurance. The guidelines on those regulations have several problems, namely the lack of clarity and provision as well as violations of the principles of legislation. As a result consumer has a very weak position. Consumer is often categorized as concurrent creditor who will receive compensation only after separatist and preferential creditor. In contrast, the positions of the curator, the administrator, the supervisory judge are too strong that it allows for irregularities such as mafia practices in bankruptcy cases that harm the consumer. With regard to legal culture, law enforcement has acknowledged the position of consumer as a creditor in bankruptcy, but conversely judge’s verdict has not favored the consumer. This makes people prefer to resolve the dispute through ways other than bankruptcy. Therefore, the Insolvency Law needs to regulate the consumer position clearly; while regulation on its supervision also needs to be strengthened; and heavy sanctions should also be ordered against any misconduct by law enforcement authorities. Concurrently other laws need to adjust their rules with Insolvency Law for effective implementation. AbstrakKepailitan dan penundaan kewajiban pembayaran utang merupakan salah satu mekanisme penyelesaian sengketa yang dapat dipilih oleh para pihak dengan tujuan menyelesaikan masalah secara singkat murah dan transparan. Mekanisme kepailitan diatur dalam UU No. 37 Tahun 2004 tentang Kepailitan dan Penundaan Kewajiban Pembayaran Utang (UU Kepailitan). Namun dalam praktiknya UU Kepailitan memiliki banyak permasalahan terutama berkaitan dengan perlindungan konsumen. Tulisan ini akan membahas pengaturan kedudukan konsumen terkait kepailitan dan implementasinya. Penulis menemukan bahwa yang mengatur kedudukan konsumen dalam kepailitan tidak hanya UU Kepailitan akan tetapi juga KUHPerdata, UU No. 8 Tahun 1999 tentang Perlindungan Konsumen, dan UU No. 40 Tahun 2014 tentang Perasuransian. Pengaturan tersebut memiliki beberapa permasalah yaitu adanya ketidakjelasan dan ketidaksingkronan pengaturan serta pelanggaran asas peraturan perundang-undangan. Akibatnya dalam pelaksanaanya kedudukan konsumen menjadi sangat lemah. Konsumen kerap dikategorikan sebagai kreditor konkuren yang akan menerima ganti kerugian setelah kreditor separatis dan preferen. Sebaliknya, kedudukan kurator, pengurus, hakim pengawas sangat kuat sehingga memungkinkan terjadi penyimpangan seperti praktik mafia kepailitan yang merugikan konsumen. Berkaitan dengan budaya hukum, penegak hukum telah mengakui kedudukan konsumen sebagai kreditor dalam kepailitan hanya saja putusan hakim belum berpihak terhadap konsumen. Hal ini membuat masyarakat lebih memilih menyelesaikan sengketa melalui cara di luar kepailitan. Oleh sebab itu UU Kepailitan perlu mengatur kedudukan konsumen secara jelas; aturan tentang pengawasan juga perlu diperketat; dan sanksi yang tegas terhadap penegak hukum yang melanggar juga perlu diatur. Sedangkan UU lain perlu menyesuaikan aturan dengan UU Kepailitan supaya dapat dilaksanakan.